2019
DOI: 10.1590/2237-6089-2017-0104
|View full text |Cite
|
Sign up to set email alerts
|

Translation and cross-cultural adaptation of the Motor Behavior Checklist (MBC) into Brazilian Portuguese

Abstract: Introduction There are only a few instruments available to assess behavioral problems in school-age children based on reports of physical education teachers. The Motor Behavior Checklist (MBC) was designed to be completed by this professional in free play-situations or during physical education classes to rate students’ motor-related behavior using 5-point Likert scales. The MBC comprises 59 items distributed into two broadband factors (externalizing and internalizing) and seven behavior problem scales: rule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The professionals, who participated at the focus group, indicated that there was a specific need for some of the items to reflect the cultural environment in schools, taking into consideration that not all students’ deviant behaviors are easy to be observed in a structured class environment in UAE schools. Furthermore, the significance of cross-cultural adaptation of the MBC for use in different countries has also been demonstrated in previous studies (e.g., Paiano et al 2019 ; Efstratopoulou et al 2012a ). Overall results are in accordance with other studies, which have also revealed that, based on the synthesized version, the translation and back-translation processes are adequate methods for translating and culturally adapting instruments, without major distortions ( Mondrzak et al 2016 ; Wild et al 2005 ; Borsa et al 2012 ; Gjersing et al 2010 ; Mattos et al 2006 ).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The professionals, who participated at the focus group, indicated that there was a specific need for some of the items to reflect the cultural environment in schools, taking into consideration that not all students’ deviant behaviors are easy to be observed in a structured class environment in UAE schools. Furthermore, the significance of cross-cultural adaptation of the MBC for use in different countries has also been demonstrated in previous studies (e.g., Paiano et al 2019 ; Efstratopoulou et al 2012a ). Overall results are in accordance with other studies, which have also revealed that, based on the synthesized version, the translation and back-translation processes are adequate methods for translating and culturally adapting instruments, without major distortions ( Mondrzak et al 2016 ; Wild et al 2005 ; Borsa et al 2012 ; Gjersing et al 2010 ; Mattos et al 2006 ).…”
Section: Discussionsupporting
confidence: 67%
“…More specifically, with the use of several assessment scales, they are asked to rate their students/children’s behaviors across a variety of settings (e.g., home, school, athletic activities, play, etc.) in common, everyday circumstances ( Paiano et al 2019 ). These behaviors are often related to problems in academic achievement, social maturity issues, and family relationships, which are usually evident in children with NDD ( Haack et al 2019 ).Furthermore, teachers, in particular, are considered as the most representative and valid source of information regarding their students’ behavioral problems, since they interact with the children on a daily basis and within the school environment, where specific behavioral patterns are expected ( Gardon 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the development of the cross-cultural adaptation process, there needs to be a defined protocol in the literature as the best one to use. However, this study shows that the steps of translation, comparison and synthesis, back--translation, comparison and determination of equivalence, pilot testing with the target population, and validation procedures are commonly used by researchers worldwide (9)(10)(11) . This information supports the choice of the Sousa and Rojjanasrirat protocol (8) for the development of this work since this protocol includes all the stages mentioned above for the translation and cross-cultural adaptation process of the Patient Safety Checklist for Outpatient Hemodialysis, confirming the reliability of the protocol used.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a combination of methods were adopted for translation and cross-cultural adaptation of the NIMH-LCM-S/P™. These methods were suggested by Borsa et al 26 Cassepp-Borges et al, 27 Gjersing et al, 28 Hungerbünler & Wang, 29 and Paiano et al 30 According to Borsa et al, 26 there is no agreement on which methodological framework cross-cultural adaptation of an instrument should follow. The adaptation depends on the characteristics of each instrument, application contexts, and target population traits.…”
Section: Methodsmentioning
confidence: 99%